Anti-reflection composition for improving oxidability of photovoltaic glass

By using sulfate, nitrate and variable valence oxide in the production of photovoltaic glass, the problem of how photovoltaic glass improves the oxidation of liquid glass to improve transmittance is solved, and the effect of improving the oxidation and transmittance of photovoltaic glass is achieved, while reducing production costs.

CN119612956APending Publication Date: 2025-03-14CHINA LUOYANG FLOAT GLASS GROUP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411919989.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

How photovoltaic glass improves the oxidation of liquid glass and thus improves its transmittance is currently lacking effective technical means.

Method used

An impermeable composition is used, which includes sulfate, nitrate and variable valence oxide, with a specific molar percentage range of: 28-31% sulfate, 60-70% nitrate, and 0-11.2% of variable valence oxide, wherein the variable valence oxide is cerium oxide, antimony oxide or tin oxide. This composition promotes the conversion of Fe2+ in the glass liquid to Fe3+ by releasing reactive oxygen, thereby improving the oxidation and transmittance of the glass.

Benefits of technology

Effectively improve the oxidation and transmittance of photovoltaic glass, reduce the use of antimony oxide, reduce production costs, and ensure product quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_5
    Figure SMS_5
Patent Text Reader

Abstract

The invention discloses an anti-reflection composition for improving the oxidability of photovoltaic glass, and relates to the technical field of photovoltaic glass production. 60-70% of nitrate; 0-11.2% of a variable valence oxide, and any one or a combination of two or more of a variable valence metal oxide cerium oxide, antimony oxide or tin oxide; after the anti-reflection composition is added, the glass oxidability of the produced photovoltaic glass is between 10% and 20%, the oxidability of the glass can be effectively controlled, and the transmittance of the photovoltaic glass is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photovoltaic glass production, and in particular to an anti-reflection composition for improving the oxidizability of photovoltaic glass. Background Art

[0002] Transmittance has always been an important factor restricting the quality of photovoltaic glass products. The key to affecting transmittance is to control the iron content of the glass. However, under the same iron content, the transmittance of photovoltaic glass is not the same. This is mainly because iron is present in the glass as Fe 2+ and Fe 3+ There are two valence states, each of which has different light absorption capabilities in different wavelength bands. 2+ There is strong absorption at a wavelength of 1050nm and extends to the visible light region. 3+ There is strong absorption at a wavelength of 380nm, and Fe 2+ The absorption coefficient is Fe 3+ The transmittance of photovoltaic glass is about ten times that of Fe. 2+ The content of Fe directly affects the transmittance of photovoltaic glass. Therefore, under the same production process and the same iron content, Fe 2+ Converted to Fe 3+ , which is crucial to improving the transmittance, and enhancing the oxidizability of the glass liquid and promoting the conversion of divalent iron into trivalent iron is one of the effective means to improve the transmittance of photovoltaic glass.

[0003] Therefore, how to improve the oxidizability of the glass liquid and increase its transmittance is a difficult problem facing the photovoltaic glass industry, and there are no relevant technical reports yet. Summary of the invention

[0004] In order to overcome the deficiencies in the background technology, the present invention provides a transmittance-enhancing composition for improving the oxidizability of photovoltaic glass. The present invention can effectively control the redox state of the glass and improve the transmittance of the photovoltaic glass.

[0005] In order to achieve the above-mentioned purpose of the invention, the present invention adopts the following technical solution: A reflective-enhancing composition for improving the oxidizability of photovoltaic glass, the reflective-enhancing composition comprising the following components in molar percentage: Sulfate 28-31%; Nitrate 60-70%; Variable valence oxides 0~11.2%.

[0006] In the anti-reflection composition for improving the oxidizability of photovoltaic glass, the variable-valence oxide is any one of cerium oxide, antimony oxide or tin oxide, or a combination of two or more thereof.

[0007] In the anti-reflection composition for improving the oxidation property of photovoltaic glass, when the variable-valence oxides are selected as cerium oxide, antimony oxide and tin oxide, the molar percentage of cerium oxide is 0-3.6%, the molar percentage of antimony oxide is 0-4.2%, and the molar percentage of tin oxide is 0-3.4%.

[0008] The anti-reflection composition for improving the oxidizability of photovoltaic glass shall meet the following requirements: 2.5≤ ≤3, and 10%≤ ≤15%; Where a is the total amount of active oxygen released by each component in the anti-reflection composition, a=0.5n(SO4 2- )+0.5n(NO3 - )+0.25n(CeO2)+n(Sb2O5)+0.5n(SnO2), where n is the molar number of each component in the composition; b is the total amount of active oxygen required for photovoltaic glass, which is the amount of Fe in the glass. 2+ Converted to Fe 3+ The total molar amount of active oxygen required; c is the molar number of total iron (expressed as Fe2O3).

[0009] The total iron content in the glass is expressed as Fe2O3 according to standard analysis, regardless of its actual presence, and the amount of iron in the ferrous state is expressed as FeO, even though it may not actually be present in the glass as FeO. A measure of the oxidizability of the glass is expressed as the FeO / total Fe2O3 ratio, which is the mole percentage of iron in the ferrous state (expressed as FeO) divided by the mole percentage of total iron in the ferric state (expressed as Fe2O3); after adding the antireflection composition, the oxidizability of the glass in the produced photovoltaic glass is between 10% and 20%.

[0010] In the anti-reflection composition for improving the oxidizability of photovoltaic glass, the sulfate is sodium sulfate.

[0011] In the anti-reflection composition for improving the oxidizability of photovoltaic glass, the nitrate is sodium nitrate.

[0012] In the antireflection composition for improving the oxidizability of photovoltaic glass, the antimony oxide is antimony pentoxide.

[0013] By adopting the above technical solution, the present invention has the following advantages: 1. Sulfate decomposes into SO2 and O2 at high temperature, which can oxidize the variable-valence oxides in the composition into high-valence states. After decomposition, oxygen is released to convert Fe in the glass liquid. 2+ Oxidized to Fe 3+ , reducing Fe 2+The molar ratio of sulfate content in the composition should be limited to 28%-31%. If the content is greater than 31%, the SO2 content produced by the decomposition of sulfate is too high and cannot be discharged in time or absorbed by the glass liquid. It will remain in the glass liquid to form bubbles and easily form a large amount of foam. Although the amount of oxygen released is large, it cannot remove the Fe in the glass. 2+ Complete oxidation will not help improve the transmittance and will also affect the product quality of photovoltaic glass.

[0014] 2. Nitrate, as an oxidant and flux, can release a large amount of O2 at low temperatures, ensuring the oxidizability of photovoltaic glass liquid at low temperatures. It can also oxidize variable-valence oxides into high-valence states. At high temperatures, variable-valence oxides release oxygen to oxidize Fe in the glass liquid. 2+ Converted to Fe 3+ ; 3. Cerium oxide is used as a high-temperature oxidant. It releases oxygen at high temperatures to 2+ Converted to Fe 3+ However, if the amount of cerium oxide added is too large, it will cause the glass to absorb ultraviolet light and affect the photovoltaic transmittance of the photovoltaic glass. When the molar ratio of cerium oxide in the composition is greater than 3.6%, the photovoltaic transmittance of the photovoltaic glass will decrease. 4. As a high-temperature oxidant, the price of antimony oxide has been rising year by year, and the increase is obvious. The molar ratio of antimony oxide in the composition of the present invention is controlled at 0-4.2%, and the effective utilization rate is higher. Compared with the prior art, the production cost of photovoltaic glass is reduced; 5. The anti-reflection composition for improving the oxidation property of photovoltaic glass of the present invention is applied to photovoltaic glass, so that the ratio of FeO / total Fe2O3 in photovoltaic glass is between 10% and 20%, thereby effectively improving the transmittance of photovoltaic glass, reducing the usage of antimony oxide, and reducing the production cost. DETAILED DESCRIPTION

[0015] The present invention can be explained in more detail by the following examples, but the present invention is not limited to the following examples; The present invention discloses an anti-reflection composition for improving the oxidizability of photovoltaic glass, wherein the anti-reflection composition comprises the following components in terms of molar percentage: Sulfate 28-31%; Nitrate 60-70%; Variable valence oxides 0~11.2%.

[0016] During implementation, the sulfate is sodium sulfate; the nitrate is sodium nitrate.

[0017] Furthermore, the variable valence oxide is any one of cerium oxide, antimony oxide or tin oxide, or a combination of two or more thereof.

[0018] In specific practice, the molar percentage of cerium oxide is 0-3.6%, the molar percentage of antimony oxide is 0-4.2%, and the molar percentage of tin oxide is 0-3.4%.

[0019] Furthermore, the antimony oxide is antimony pentoxide.

[0020] Furthermore, the anti-reflection composition for improving the oxidizability of photovoltaic glass shall satisfy the following requirements: 2.5≤ ≤3, and 10%≤ ≤15%; Where a is the total amount of active oxygen released by each component in the anti-reflection composition, a=0.5n(SO4 2- )+0.5n(NO3 - )+0.25n(CeO2)+n(Sb2O5)+0.5n(SnO2), where n is the molar number of each component in the composition; b is the total molar number of active oxygen required for photovoltaic glass, which is the amount of Fe in the glass. 2+ Converted to Fe 3+ The total number of moles of active oxygen required; c is the number of moles of total iron (expressed as Fe2O3).

[0021] In addition, the measure of glass oxidation is expressed as the ratio of FeO / total Fe2O3, which is the molar percentage of iron converted from divalent iron to trivalent iron divided by the molar percentage of total iron (expressed as Fe2O3); after adding the anti-reflection composition, the glass oxidation in the produced photovoltaic glass is between 10% and 20%.

[0022] In the specific implementation of the present invention, the anti-reflection composition for improving the oxidation property of photovoltaic glass is composed of sulfate, nitrate and variable valence oxide, wherein the variable valence oxide is any one of cerium oxide, antimony oxide and tin oxide or a combination of two or more thereof, and the composition (molar percentage) of the anti-reflection composition is: Sodium sulfate: 28-31%; Sodium nitrate: 60-70%; Cerium oxide: 0-3.6%; Antimony oxide: 0-4.2%; Tin oxide: 0-3.4%.

[0023] Wherein, the measure of the oxidizability of the glass is expressed as the ratio FeO / total Fe2O3, which is the mole percentage of iron in the ferrous state (expressed as FeO) divided by the mole percentage of total iron in the ferric state (expressed as Fe2O3); In a specific implementation, the composition (in mole percentage) of the photovoltaic glass used to verify the photovoltaic glass oxidative anti-reflection composition of the present invention is: Silicon dioxide 71.08%, calcium oxide 9.17%, magnesium oxide 5.49%, aluminum oxide 0.59%, R2O 13.67%; Examples 1-6 and Comparative Example 1 selected a total iron content of 0.005 mol%, and Examples 7-12 and Comparative Example 2 selected an iron content of 0.004 mol%.

[0024] When the present invention is implemented, the main preparation steps of the glass test sample are: weighing-mixing-melting-forming-annealing-processing-performance testing.

[0025] Specific steps: After weighing the glass components according to the weight percentage table, mix them thoroughly, pour the mixed raw materials into the crucible, keep them at 1440-1500℃ for 2h, and after clarifying and homogenizing, reduce the temperature to the temperature range required for molding, and perform molding annealing. After the glass is cooled, cut, grind and polish the glass sample to make a 70mm×70mm×2mm block sample for transmittance test.

[0026] After the sample was ground into powder, the Fe content in the glass was determined by chemical analysis. 2+ , total iron content test.

[0027] The transmittance of ultra-white glass was measured using an Agilent cary-5000 UV-visible-near-infrared spectrophotometer.

[0028] Embodiment 1: A transmittance-enhancing composition for improving the oxidation property of photovoltaic glass, wherein the total Fe2O3 content in 100mol of photovoltaic glass is 0.005mol, and the composition comprises the following components: sodium sulfate, sodium nitrate, cerium oxide, and antimony oxide. 0.004mol of the transmittance-enhancing composition needs to be added, and the composition (in molar percentage) is: 30% sodium sulfate, 63% sodium nitrate, 3% cerium oxide, and 4% antimony oxide.

[0029] Embodiment 2: A transmittance-enhancing composition for improving the oxidation property of photovoltaic glass, wherein the total Fe2O3 content in 100mol of photovoltaic glass is 0.005mol, and the composition comprises the following components: sodium sulfate, sodium nitrate, cerium oxide, and antimony oxide. 0.004mol of the transmittance-enhancing composition needs to be added, and the composition (in molar percentage) is: 30% sodium sulfate, 65% sodium nitrate, 2% cerium oxide, and 3% antimony oxide.

[0030] Embodiment 3: A transmittance-enhancing composition for improving the oxidation property of photovoltaic glass, wherein the total Fe2O3 content in 100mol of photovoltaic glass is 0.005mol, and the composition comprises the following components: sodium sulfate, sodium nitrate, cerium oxide, and antimony oxide. It is necessary to add 0.004mol of the transmittance-enhancing composition, wherein the composition (in molar percentage) is: 29% sodium sulfate, 68% sodium nitrate, 1% cerium oxide, and 2% antimony oxide.

[0031] Embodiment 4: A transmittance-enhancing composition for improving the oxidation property of photovoltaic glass, wherein the total Fe2O3 content in 100mol of photovoltaic glass is 0.005mol, and the composition comprises the following components: sodium sulfate, sodium nitrate, cerium oxide, and antimony oxide. 0.004mol of the transmittance-enhancing composition needs to be added, and the composition (in molar percentage) is: 29% sodium sulfate, 69% sodium nitrate, 1% cerium oxide, and 1% antimony oxide.

[0032] Embodiment 5: A transmittance-enhancing composition for improving the oxidation property of photovoltaic glass, wherein the total Fe2O3 content in 100mol of photovoltaic glass is 0.005mol, and the composition comprises the following components: sodium sulfate, sodium nitrate, cerium oxide, and tin oxide. 0.004mol of the transmittance-enhancing composition needs to be added, and the composition (in molar percentage) is: 30% sodium sulfate, 65% sodium nitrate, 2% cerium oxide, and 3% tin oxide.

[0033] Embodiment 6: A transmittance-enhancing composition for improving the oxidation property of photovoltaic glass, wherein the total Fe2O3 content in 100mol of photovoltaic glass is 0.005mol, and the composition comprises the following components: sodium sulfate, sodium nitrate, antimony oxide, and tin oxide. 0.004mol of the transmittance-enhancing composition needs to be added, and the composition (in molar percentage) is: 29% sodium sulfate, 66% sodium nitrate, 4% antimony oxide, and 1% tin oxide.

[0034] Comparative Example 1: A commercially available glass, the total iron content in 100 mol of photovoltaic glass is 0.005 mol, and 0.35 mol of Glauber's salt is added.

[0035] Embodiment 7: A transmittance-enhancing composition for improving the oxidation property of photovoltaic glass, wherein the total Fe2O3 content in 100mol of photovoltaic glass is 0.004mol, and the composition comprises the following components: sodium sulfate, sodium nitrate, cerium oxide, and antimony oxide. It is necessary to add 0.003mol of the transmittance-enhancing composition, wherein the composition (in molar percentage) is: 30% sodium sulfate, 63% sodium nitrate, 3% cerium oxide, and 4% antimony oxide.

[0036] Embodiment 8: A transmittance-enhancing composition for improving the oxidation property of photovoltaic glass, wherein the total Fe2O3 content in 100mol of photovoltaic glass is 0.004mol, and the composition comprises the following components: sodium sulfate, sodium nitrate, cerium oxide, and antimony oxide. 0.003mol of the transmittance-enhancing composition needs to be added, and the composition (in molar percentage) is: 30% sodium sulfate, 65% sodium nitrate, 2% cerium oxide, and 3% antimony oxide.

[0037] Embodiment 9: A transmittance-enhancing composition for improving the oxidation property of photovoltaic glass, wherein the total Fe2O3 content in 100mol of photovoltaic glass is 0.004mol, and the composition comprises the following components: sodium sulfate, sodium nitrate, cerium oxide, and antimony oxide. It is necessary to add 0.003mol of the transmittance-enhancing composition, wherein the composition (in molar percentage) is: 29% sodium sulfate, 68% sodium nitrate, 1% cerium oxide, and 2% antimony oxide.

[0038] Embodiment 10: A transmittance-enhancing composition for improving the oxidation property of photovoltaic glass, wherein the total Fe2O3 content in 100mol of photovoltaic glass is 0.004mol, and the composition comprises the following components: sodium sulfate, sodium nitrate, cerium oxide, and antimony oxide. 0.003mol of the transmittance-enhancing composition needs to be added, and the composition (in molar percentage) is: 29% sodium sulfate, 69% sodium nitrate, 1% cerium oxide, and 1% antimony oxide.

[0039] Embodiment 11: A transmittance-enhancing composition for improving the oxidation property of photovoltaic glass, wherein the total Fe2O3 content in 100mol of photovoltaic glass is 0.004mol, and the composition comprises the following components: sodium sulfate, sodium nitrate, cerium oxide, and tin oxide. 0.003mol of the transmittance-enhancing composition needs to be added, and the composition (in molar percentage) is: 30% sodium sulfate, 65% sodium nitrate, 2% cerium oxide, and 3% tin oxide.

[0040] Embodiment 12: A transmittance-enhancing composition for improving the oxidation property of photovoltaic glass, wherein the total Fe2O3 content in 100mol of photovoltaic glass is 0.004mol, and the composition comprises the following components: sodium sulfate, sodium nitrate, antimony oxide, and tin oxide. 0.003mol of the transmittance-enhancing composition needs to be added, and the composition (in molar percentage) is: 29% sodium sulfate, 66% sodium nitrate, 4% antimony oxide, and 1% tin oxide.

[0041] Comparative Example 2: A commercially available glass has a total iron content of 0.004 mol per 100 mol of glass, and 0.3 mol of Glauber's salt is added.

[0042]

[0043] From the comparison between the embodiment and the comparative example, it can be seen that after the addition of the oxidative anti-reflection composition of the present invention, the oxidizability of the photovoltaic glass can be effectively improved, and the photovoltaic transmittance of the photovoltaic glass can be improved, and the amount of the oxidative anti-reflection composition in the embodiment is much less than that in the comparative example. With the increase of the oxygen release amount of the oxide in the oxidative anti-reflection composition, the FeO / total Fe2O3 ratio of the photovoltaic glass decreases, and the photovoltaic transmittance of the photovoltaic glass increases.

[0044] Parts of the present invention not described in detail are prior art.

[0045] The embodiments selected herein for the purpose of disclosing the invention are currently considered to be suitable, but it should be understood that the invention is intended to include all changes and modifications of the embodiments that fall within the scope of the concept and invention.

Claims

1. A reflective enhancement composition for improving the oxidizability of photovoltaic glass, characterized by: The antireflection composition comprises the following components in molar percentage: Sulfate 28-31%; Nitrate 60-70%; Variable valence oxides 0~11.2%.

2. The anti-reflection composition for improving the oxidizability of photovoltaic glass according to claim 1, characterized in that: The variable valence oxide is any one of cerium oxide, antimony oxide or tin oxide, or a combination of two or more thereof.

3. The anti-reflection composition for improving the oxidizability of photovoltaic glass according to claim 2, characterized in that: When the variable valence oxide is selected from cerium oxide, antimony oxide and tin oxide, the molar percentage of cerium oxide is 0-3.6%, the molar percentage of antimony oxide is 0-4.2%, and the molar percentage of tin oxide is 0-3.4%.

4. The anti-reflection composition for improving the oxidizability of photovoltaic glass according to claim 1, characterized in that: The antireflection composition must meet the following requirements: 2.5≤ ≤3, and 10%≤ ≤15%; Where a is the total amount of active oxygen released by each component in the anti-reflection composition, a=0.5n(SO4 2- )+0.5n(NO3 - )+0.25n(CeO2)+n(Sb2O5)+0.5n(SnO2), where n is the molar number of each component in the composition; b is the total amount of active oxygen required for photovoltaic glass, which is the amount of Fe in the glass. 2+ Converted to Fe 3+ The total molar amount of active oxygen required; c is the molar number of total iron (expressed as Fe2O3).

5. The anti-reflection composition for improving the oxidizability of photovoltaic glass according to claim 1, characterized in that: The sulfate is sodium sulfate.

6. The anti-reflection composition for improving the oxidizability of photovoltaic glass according to claim 1, characterized in that: The nitrate is sodium nitrate.

7. The anti-reflection composition for improving the oxidizability of photovoltaic glass according to claim 1, characterized in that: The antimony oxide is antimony pentoxide.